Perianal-Perineal Localized Alveolar-Embryonal (Mixed) Type Rhabdomyosarcoma: Rare Localization, Case Report - Yasemin Durum; Hakan Maral; Mustafa Gök; Canten Tataroğlu (Galenos Yayinevi, 2017)
A 17-year old girl who had been admitted to another hospital with perianal swelling and pain was diagnosed with perianal abscess. She had been given anti-biotheraphy and anti-inflamatory medication. Because her swelling and pain got worse, she was referred to our pediatric clinic. After her physical examination, she was prediagnosed with perianal abscess/tumor, and reffered to our department for magnetic resonance imaging examination, after which she was diagnosed with perianal tumor, and biopsy was performed. Alveolar-embryonal (mixed) type rhabdomyosarcoma (RMS) was diagnosed in the histopathology. Even though RMS is diagnosed frequently in childhood and adolescence, perianal and perineal location for this tumor is relatively rare. We wanted to highlight the rare localization and possible differential diagnosis for this type of tumor.